2020
DOI: 10.1186/s12872-020-01568-0
|View full text |Cite
|
Sign up to set email alerts
|

Significant association between rs28362491 polymorphism in NF-κB1 gene and coronary artery disease: a meta-analysis

Abstract: Background: The association of rs28362491 polymorphism in NF-κB1 gene and coronary artery disease (CAD) risk was reported in several studies with inconsistent outcomes. This study aimed to comprehensively collect and synthesize the existing evidence to appraise whether rs28362491 was correlated to CAD susceptibility. Methods: Databases of Web of Science, EMBASE, PubMed, Wanfang, and CNKI were retrieved from inception to August 1, 2019 without any restriction on language. The strengths of association between rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…SNP rs28362491 in the ubiquitous transcription factor NF- κΒ was reported to be involved in the expression of immune-modulating genes due to its impact on NF- κΒ gene transcription [ 41 ]. Therefore, this SNP has been implicated in inflammatory diseases including cardiovascular diseases [ 14 ]. In the meta-analysis by Wang et al, the deletion allele was shown to be associated with CV diseases even after stratification by ethnicity and gender [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SNP rs28362491 in the ubiquitous transcription factor NF- κΒ was reported to be involved in the expression of immune-modulating genes due to its impact on NF- κΒ gene transcription [ 41 ]. Therefore, this SNP has been implicated in inflammatory diseases including cardiovascular diseases [ 14 ]. In the meta-analysis by Wang et al, the deletion allele was shown to be associated with CV diseases even after stratification by ethnicity and gender [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this SNP has been implicated in inflammatory diseases including cardiovascular diseases [ 14 ]. In the meta-analysis by Wang et al, the deletion allele was shown to be associated with CV diseases even after stratification by ethnicity and gender [ 14 ]. However, a corresponding association could not be confirmed in the present study in the cohort of CV patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, NFKBIZ variant was an independent risk factor for developing early-onset CAD [ 50 ]. However, in a recent meta-analysis of 13 case-control studies with 17 individual cohorts containing 9378 cases and 10,738 controls, the mutant D allele in NFKB1 rs28362491 locus increased the risk of CAD [ 51 ].…”
Section: Nf-κb Genetic Variants and Cardiometabolic Comorbiditymentioning
confidence: 99%